Toll-like Receptor-mediated Inflammatory Signaling Reprograms Cardiac Energy Metabolism by Repressing Peroxisome Proliferator-activated Receptor γ Coactivator-1 (PGC-1) Signaling - Schilling, Joel (2011)
BACKGROUND: Currently, there are no specific therapies available to treat cardiac dysfunction due to sepsis and other chronic inflammatory conditions. Activation of toll-like receptor 4 (TLR4) by lipopolysaccharide (LPS) is an early event in gram-negative bacterial sepsis, triggering a robust inflammatory response and changes in metabolism. PPARγ coactivator-1 (PGC-1) α and β serve as critical physiological regulators of energy metabolic gene expression in heart. METHODS AND RESULTS: Injection of mice with LPS triggered a myocardial fuel switch similar to that of the failing heart; reduced mitochondrial substrate flux and myocyte lipid accumulation. The LPS-induced metabolic changes were associated with diminished ventricular function and suppression of the genes encoding PGC-1α and β, known transcriptional regulators of mitochondrial function. This cascade of events required TLR4 and NF-κB activation. Restoration of PGC-1β expression in cardiac myocytes in culture and in vivo in mice reversed the gene regulatory, metabolic, and functional derangements triggered by LPS. Interestingly, the effects of PGC-1β overexpression were independent of the upstream inflammatory response, highlighting the potential utility of modulating downstream metabolic derangements in cardiac myocytes as a novel strategy to prevent or treat sepsis-induced heart failure. CONCLUSIONS: LPS triggers cardiac energy metabolic reprogramming via suppression of PGC-1 coactivators in the cardiac myocyte. Reactivation of PGC-1β expression can reverse the metabolic and functional derangements caused by LPS-TLR4 activation, identifying the PGC-1 axis as a candidate therapeutic target for sepsis-induced heart failure.